2014
DOI: 10.1021/jp5068022
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights in the Structure and Layered Assembly of Polyelectrolytes at the Oil/Water Interface

Abstract: Macromolecular assembly at the interface between water and a hydrophobic surface underlies some of the most important biological and environmental processes on the planet. Important model systems for understanding this assembly at such interfaces are polyelectrolytes that have hydrophilic units interspersed along a hydrophobic polymer backbone, similar to many biological macromolecules. This feature article provides recent advances in the molecular factors that contribute to the adsorption and assembly of carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 92 publications
3
37
0
Order By: Relevance
“…Khanamiri et al 24 demonstrated that Ca 2+ is conductive to lower IFT and changes the oil-water interfacial elastic modulus. Some technologies have been proposed to investigate the oil-water interface, such as surface second harmonic generation, 25 small-angle neutron scattering 26 and vibrational sum-frequency spectroscopy, 27 but the dynamics of ions or molecules near the interface are not fully addressed. The molecular dynamics (MD) method which can be used to obtain the detailed microscopic structures is a powerful tool to investigate the macroscopic properties of the oil-water interface with the applicability of the statistical mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Khanamiri et al 24 demonstrated that Ca 2+ is conductive to lower IFT and changes the oil-water interfacial elastic modulus. Some technologies have been proposed to investigate the oil-water interface, such as surface second harmonic generation, 25 small-angle neutron scattering 26 and vibrational sum-frequency spectroscopy, 27 but the dynamics of ions or molecules near the interface are not fully addressed. The molecular dynamics (MD) method which can be used to obtain the detailed microscopic structures is a powerful tool to investigate the macroscopic properties of the oil-water interface with the applicability of the statistical mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Previous measurements on polyacrylic acid (PAA) at water/air and water/oil interface also showed a high sensitivity of the degree of accumulation at the surface on the pH value. 25,[53][54][55] For PAA solutions, it was observed that increasing the bulk pH led to polymer depletion from the surface because of the relative increase of carboxylate anion groups with respect to the COOH. In this context, it is remarkable and surprising that in the case of hyaluronan, depletion from the surface occurs upon lowering of the pH value.…”
Section: Effect Of Ph On the Surface Accumulation Of Hyaluronanmentioning
confidence: 99%
“…It has been reported that the adsorption of HPAM on the oil-water interface increases the steric barriers of dispersed oil droplets, which leads to the enhanced stability of oil/water emulsion [16,[26][27][28]. Polymers (such as polystyrene sulfonate sodium, PSS) have the ability to form complexes with the oppositely charged molecules (such as hexadecanetrimethyl-ammonium bromide, CTAB) by electrostatic attraction or hydrophobic interaction [29,30].…”
Section: Interfacial Tension and Dilational Rheology Analysis Of The mentioning
confidence: 99%